Synthesis, antiviral and anticancer activity of some novel thioureas derived from N-(4-nitro-2-phenoxyphenyl)-methanesulfonamide - KÜÇÜKGÜZEL, İLKAY; KARAKUŞ, SEVGİ; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2009)
Due to a continuing effort to develop new antiviral agents, a series of 1-[4-(methanesulfonamido)-3-phenoxyphenyl]-3-alkyl/aryl thioureas 3a-i have been synthesized by the reaction of alkyl/aryl isothiocyanates with 4-amino-2-phenoxymethanesulfonanilide. These derivatives were structurally characterized by the use of spectral techniques and evaluated for their anticancer and antiviral activities. None of the tested compounds showed significant anticancer properties on A549 and L929 cell lines. All synthesized compounds 3a-i were evaluated in vitro against HIV-1 (IIIB) and HIV-2 (ROD) strains in MT-4 cells, as well as other selected viruses such as HSV-1, HSV-2, Coxsackie virus B4, Sindbis virus and varicella-zoster virus using HEL, HeLa and Vero cell cultures. Compound 3b was able to block HIV replication with almost 100% maximum protection at 125 mu g/ml, and IC50 values of 54.9 mu g/ml and 65.9 mu g/ml against HIV-1 and HIV-2, respectively. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: Nimesulide; Thiourea; Antiviral activity; Anticancer activity; BREAST-CANCER CELLS; AROMATASE EXPRESSION; INHIBITORS; HIV; NIMESULIDE; ANALOGS; VIRUS